A molecular investigation of a mixed ancestry family displaying dementia and movement disorders - Abrahams-Salaam, Fatima (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScMedSc (Biomedical Sciences. Molecular Biology and Human Genetics))--Stellenbosch University, 2008.